Metode Pembagian Harta Bersama Pasca Cerai Mati Di Desa Pandanarum Kecamatan Sutojayan Blitar - Arifin, Mochammad (Universitas Nahdlatul Ulama Blitar, 2023)
Joint assets are assets acquired during a legal marriage. Husband and wife have the same rights and obligations over joint property. In the practice of implementing law in the community,especially regarding the distribution of joint assets, there are variations/diversities in accordance with the customary provisions and habits of each region. In this regard, this research is focused on examining the method of sharing joint assets after divorce in Pandanarum Village, Blitar Regency. This research uses a qualitative method with a phenomenological approach, phenomenology is a type of qualitative research that looks at and looks more closely and in detail about individual explanations and understanding of their experiences. Data is collected by data reduction methods, data display, and verification or drawing conclusions. The results of this study indicate that in the practice of the Pandanarum village community, marriages that break up due to death then all assets become inheritance assets. if the husband dies first, then all assets become inheritance and are distributed to heirs based on fiqh provisions. The wife in this case only gets 1/8 if there are children and ¼ if there are no children. Meanwhile, if the wife dies first, usually the assets will not be divided until the husband dies. Keywords : Distribution of Wealth, death divorce